PERLINDUNGAN HUKUM TERHADAP PEMEGANG HAK CIPTA FILM BIOSKOP YANG DITAYANGKAN PADA MEDIA SOSIAL - Anggrayni, Liza; Bhakti, Rizki Tri Anugrah (SCIENTIA JOURNAL, 2020)
Copyright is the exclusive right for the creator or recipient of the right to announce or reproduce his work or give permission for it by not reducing restrictions in accordance with applicable laws and regulations. Cinema film is one of the works that has a copyright, but many Indonesian people broadcast cinema films without the permission of copyright holders on social media. The purpose of this study is for copyright holders to know what kind of protection is provided by legislation in Indonesia and what efforts so that broadcasting without permission does not occur. Based on the theory of legal protection that is used by the writer to examine normatively the legislation in force in Indonesia. Legal protection can be said as a separate description of the function of the law itself, which has the concept that the law provides justice, order, certainty, usefulness and peace. In preventive protection is preventive meaning this form of protection aims to prevent the occurrence of a violation of copyright, especially in the film. This protection provides prevention to reduce piracy or duplication of films that can cause harm. Broadcasting of this film is carried out using the internet media so that it is closely related to Law concerning Information and Electronic Transactions. There is also repressive legal protection which is the final protection in the form of sanctions such as fines, imprisonment and additional punishment given if a dispute has occurred or a violation has been committed. Lack of public understanding of copyright protection results in rampant broadcasting of cinema films without permission. Keywords: Broadcast without permission, Cinema Film, Copyright.